2009
DOI: 10.1021/np800769g
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Glucuronides and a Chromone from the Aquatic Macrophyte Stratiotes aloides

Abstract: The first phytochemical analysis of the aquatic macrophyte Stratiotes aloides afforded two new flavonoid glucuronides, luteolin 7-O-beta-D-glucopyranosiduronic acid-(1-->2)-beta-D-glucopyranoside (1) and chrysoeriol 7-O-beta-D-glucopyranosiduronic acid-(1-->2)-beta-D-glucopyranoside (2), as well as the new 2-(2-hydroxypentyl)-5-carboxy-7-methoxychromone (5) and chrysoeriol 7-O-beta-(6-O-malonyl)glucopyranoside (3), which has been assigned via NMR data for the first time. Additionally, free amino acids such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Different from 3, acid hydrolysis of 4 afforded D-glucuronic acid, which was determined by GC analysis of its derivative. Another sugar unit was also identified to be arabinose by comparison of the NMR data with those reported in the literature [14,15]. However, HMBC correlation between H-1′′ (δ H 5.27) and C-4′′ (δ C 83.2), as well as the ROESY correlations between H 2 -5′′ (δ H 3.57 and 3.43) and H-1′′ (δ H 5.27)/H-3′′ (δ H 4.09) were observed, indicating that the arabinose unit in 4 was arabinofuranose instead of arabinopyranose in 1-3.…”
Section: -(45-dimethylthiazol-2-yl)-25-diphenyl Tetrazolium Bromidmentioning
confidence: 80%
“…Different from 3, acid hydrolysis of 4 afforded D-glucuronic acid, which was determined by GC analysis of its derivative. Another sugar unit was also identified to be arabinose by comparison of the NMR data with those reported in the literature [14,15]. However, HMBC correlation between H-1′′ (δ H 5.27) and C-4′′ (δ C 83.2), as well as the ROESY correlations between H 2 -5′′ (δ H 3.57 and 3.43) and H-1′′ (δ H 5.27)/H-3′′ (δ H 4.09) were observed, indicating that the arabinose unit in 4 was arabinofuranose instead of arabinopyranose in 1-3.…”
Section: -(45-dimethylthiazol-2-yl)-25-diphenyl Tetrazolium Bromidmentioning
confidence: 80%
“…Compound 5 was identified as 5,5 0 -oxybis-1,3-benzenediol (Masae, Mikiko, Kyoko, & Shuzo, 1994 181.8, 106.5, 162.4, 105.3, 163.8, 95.4, 157.6, 122.5, 114.3, 147.6, 151.7, 116.4, 119.3, 99.7, 74.5, 75.6, 71.4, 75.5, 61.2. Compound 7 was characterized as 5,3 0 ,4 0 -trihydroxyflavanone 7-glucoside (Conrad et al, 2009). …”
Section: Extraction and Isolationmentioning
confidence: 99%
“…To date there have been few studies on the chemical composition of S. aloides L. leaves. Previous phyto-chemical assays included only a comparative analysis of the total content of polyphenolic compounds in various types of leaves of selected aquatic plants (Smolders et al 2000), and the qualitative composition of flavonoids found in the leaves of a given plant (Conrad et al 2009). Species with submerged leaves showed a significantly lower phenolic content than species with emergent or floating leaves (Smolders et al 2000).…”
Section: Discussionmentioning
confidence: 99%